Geochemistry and mineralogy of rare Earth elements - Lipin, Bruce R.; McKay, G. A. (Reviews in mineralogy ;, 2019)
Volume 21 of Reviews in Mineralogy treats a short course on the rare earth elements to about 80 participants in San Francisco, California, December 1-3, 1989, just prior to the fall meeting of the American Geophysical Union. Contents:Cosmochemistry of the Rare Earth Elements: Condensation and Evaporation ProcessesRadiogenic Isotope Geochemistry of Rare Earth ElementsPartitioning of Rare Earth Elements between Major Silicate Minerals and Basaltic MeltsAn Approach to Trace Element Modeling Using a Simple Igneous System as an ExampleRare Earth Elements in Upper Mantle RocksRare Earth Elements in Metamorphic RocksRare Earth Elements in Sedimentary Rocks: Influence of Provenance and Sedimentary ProcessesAqueous Geochemistry of Rare Earth ElementsRare Earth Elements in Lunar MaterialsCompositional and Phase Relations among Rare Earth Element MineralsEconomic Geology of Rare Earth MineralsCathodoluminescence Emission Spectra of Rare Earth Element Activators in Minerals.